2019
DOI: 10.1097/01.aog.0000559146.89836.91
|View full text |Cite
|
Sign up to set email alerts
|

Why Do You Want It Out?: Provider Perspectives on Early LARC Removal [7S]

Abstract: INTRODUCTION: Providers promote long-acting reversible contraception (LARC) because LARCs are highly effective at preventing pregnancy. The FDA recommends a maximum length of time for LARC use, but not a minimum. When women requesting early LARC removal perceive resistance from their providers, frustration and damaged patient-provider relationships can result. Understanding provider attitudes and practices about LARC removal is vital to patient-centered care. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…While HCPs generally agreed that removal should be granted, some voiced a degree of reluctance. Although such reluctance is at odds with the principle of patient autonomy central to PCC, it is in line with previous research pointing patients who have met resistance when wanting to have their copper IUDs removed [26,32,35,99,104,105,111]. In correspondence with our results, previous research also indicates that some caregivers have leaned toward coercive practices to encourage LARC use [31,106], including resisting LARC removal (e.g.…”
Section: Identifying Limitations In and Developing Pccsupporting
confidence: 92%
See 2 more Smart Citations
“…While HCPs generally agreed that removal should be granted, some voiced a degree of reluctance. Although such reluctance is at odds with the principle of patient autonomy central to PCC, it is in line with previous research pointing patients who have met resistance when wanting to have their copper IUDs removed [26,32,35,99,104,105,111]. In correspondence with our results, previous research also indicates that some caregivers have leaned toward coercive practices to encourage LARC use [31,106], including resisting LARC removal (e.g.…”
Section: Identifying Limitations In and Developing Pccsupporting
confidence: 92%
“…Morison et al [ 33 ] note that expert-directed decision-making in contraceptive care, in which patient knowledge or concerns are not considered, may lead to covert patient resistance through discontinuation of contraceptive use. Poor PCC in contraceptive care can also damage the patient-provider relationship [ 34 , 104 , 105 ] and increase distrust in healthcare [ 26 , 106 ]. In other contexts too, such as among patients with contested diseases [ 107 ], distrust in medicine and withdrawal from care-seeking have been related to experiences of feeling deprioritized or badly treated by caregivers [ 6 , 39 , 40 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…U. 39 In addition to deceptive and forced sterilizations, contraceptive coercion practices that focus on those with low incomes and people of color are not only historical but continue to the present day. Oral contraceptive experimentation without consent on Puerto Rican women in the 1950s, mandates making receipt of public assistance contingent on the use of contraceptive implants or injections beginning in the 1990s, and contraceptive initiatives directed toward certain marginalized communities, ongoing even today, are all examples of reproductive injustices in this country.…”
Section: Obstetrician-gynecologists and Other Reproductive Health Car...mentioning
confidence: 99%
“…Participants who were offered a range of contraceptive options and time for deliberation described greater autonomy and satisfaction. 39 Another study indicated that patients, particularly people of color, felt that their preferences regarding contraceptive selection or removal were not honored due to health care practitioner biases and systemic racism. 40 Health care professionals should provide all patients with comprehensive, scientifically accurate information about the full range of available contraceptive options.…”
Section: Obstetrician-gynecologists and Other Reproductive Health Car...mentioning
confidence: 99%